A successful strategy for Preimplantation Genetic Diagnosis of beta-thalassemia and simultaneous detection of Down's syndrome using multiplex fluorescent PCR - Piyamongkol W. (2014)
Objectives: Preimplantation Genetic Diagnosis (PGD) is an alternative to prenatal diagnosis providing couples the chance to start a pregnancy with an unaffected fetus. The objective of the present study was to develop and apply quick, sensitive and accurate single cell PCR protocols for PGD of beta-thalassemia and Down's syndrome detection. Material and Method: Two couples carrying beta-thalassemia codon41-42 mutation underwent routine IVF procedures. Embryo biopsy was performed on Day-3 post-fertilisation and single cell multiplex fluorescent PCR was employed for mutation analysis, contamination detection and diagnosis of trisomy 21 cases. Results: Seventeen embryos were tested in two clinical PGD cycles. This resulted in the first birth following PGD for a single gene disorder in Thailand and South East Asia, confirmed by prenatal testing. Two embryos were shown to be affected by Down's syndrome. Conclusion: Successful strategy for PGD of beta-thalassemia and Down's syndrome detection using multiplex fluorescent PCR was introduced.